DEVELOPMENT OF ENTREPRENEURSHIP AMONG ALUMNI OF SMK NEGERI 1 CALANG - Rina Murfiana; Fikriah Noer; Rosmala Dewi (Jurnal Ilmiah Mahasiswa Pendidikan Kesejahteraan Keluarga, 2016)
SMK Negeri 1 Calang graduates are graduates who are prepared for entrepreneurship, equipped science with entrepreneurship so as to encourage them to be able to self-employment or entrepreneurship, because entrepreneurship is very important in improving the economy of a region. This study aims to determine the development of entrepreneurship among alumni of SMK Negeri 1 Calang in entrepreneurship, motivation alumni of SMK Negeri 1 Calang in entrepreneurship, and the factors that hinder the development of entrepreneurial alumni of SMK Negeri 1 Calang in entrepreneurship. This study used a qualitative approach, the subject is taken by purposive sampling technique. The data collection is done by observation, interviews, and documentation. The results showed that the alumni of SMK Negeri 1 Calang particular dressmaking department has developed a sewing business fashion, in the form of business and dressmaker atelier. Alumni SMK Negeri 1 Calang is motivated to develop the business to apply the knowledge they have owned and family income, the inhibiting factors encountered in entrepreneurship is the lack of capital, inadequate facilities, and are not adept at changing fashion models are complicated. It was concluded that the respondents in the development of an increasing number of consumers, and improving the quality of products produced. Alumni SMK Negeri 1 Calang who have developed or open a business to be more creative, innovative in creating the latest fashion models favored by consumers and more confident to take risks in business. In addition to the government of Aceh Jaya, in particular to the Head of Krueng Sabee to pay attention to vocational graduates who have opened businesses, and help them as providing capital and facilities.